Ink composition for inkjet, method for producing the same, light conversion layer, and color filter

CN122898176APending Publication Date: 2026-10-13TOPPAN HOLDINGS INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202611312851.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-07-21
Filing Date
2018-07-19
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]然而,就上述采用光刻法的滤色器的制造方法而言,由于该制造方法的特征,有如下缺点:包含较昂贵的发光性纳米晶体粒子的像素部以外的抗蚀剂材料造成浪费

Benefits of technology

[0060]能够提供提高了在大气中的稳定性的油墨组合物及其制造方法、以及使用了该油墨组合物的光转换层和滤色器。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898176A_ABST
    Figure CN122898176A_ABST
Patent Text Reader

Abstract

The present application provides an ink composition for inkjet, a method for producing the same, a light conversion layer, and a color filter. The ink composition for inkjet contains luminescent nanocrystal particles, a photopolymerizable compound, light-scattering particles, and a polymeric dispersant, the photopolymerizable compound has a LogP value of -1.0 or more and 5.0 or less, the content of the luminescent nanocrystal particles in the ink composition is 5% by mass or more based on the mass of nonvolatile components of the ink composition, the content of the light-scattering particles in the ink composition is 1% by mass or more based on the mass of nonvolatile components of the ink composition, the photopolymerizable compound contains an alicyclic epoxy monomer and an oxetane monomer, the polymeric dispersant has a weight average molecular weight of 750 or more and 30,000 or less and an acid value of 1 to 150 mgKOH / g or an amine value of 1 to 200 mgKOH / g, the viscosity of the ink composition for inkjet is 2 to 20 mPa·s, and the ink composition for inkjet is for a color filter.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application No. 201880044962.3, filed on July 19, 2018, entitled "Ink Composition and Method for Manufacturing the Same Thereof, Light Conversion Layer and Color Filter". Technical Field

[0002] This invention relates to ink compositions and methods for manufacturing the same, light conversion layers, and color filters. Background Technology

[0003] In the past, color filter pixels in displays such as liquid crystal display devices were manufactured by photolithography using a curable photoresist material containing red or green organic pigment particles, as well as alkali-soluble resin and / or acrylic monomers.

[0004] In recent years, there has been a strong demand for low power consumption in displays, and methods have been actively researched for using luminescent nanocrystal particles such as quantum dots, quantum rods, and other inorganic phosphor particles to replace the aforementioned red or green organic pigment particles in forming color filter pixels such as red pixels and green pixels.

[0005] However, the aforementioned method for manufacturing color filters using photolithography has the following drawbacks due to its characteristics: it results in waste of resist material other than the pixel portion, which contains relatively expensive luminescent nanocrystal particles. Therefore, in order to avoid such waste of resist material, research began on forming the pixel portion of the light conversion substrate using inkjet printing.

[0006] In such ink compositions, various substances are known to be used as photopolymerizable compounds. However, there is no insight into which photopolymerizable compound, which properties must be satisfied to ensure that the light conversion layer composed of its cured product does not have any defects. In practice, any photopolymerizable compound is cured to form a light conversion layer, and the light conversion layer is tested for various properties. Based on repeated exploration, the presence or absence of defects is confirmed.

[0007] In addition, for inks containing quantum dots composed of luminescent nanocrystal particles, there is a problem of deterioration caused by the infiltration of moisture from the air.

[0008] Patent document 1 discloses a blend containing a solvent saturated or supersaturated with an inert gas and a functional organic material, and also discloses a blend in which the total amount of oxygen and moisture is below a certain level.

[0009] However, patent document 1 does not describe the use of photocurable compounds.

[0010] Furthermore, no actual measurement data on moisture content was provided, and it is unclear what kind of impact different levels of moisture would have.

[0011] Furthermore, regarding the organic light-emitting materials for OLEDs, the examples show the influence of the atmosphere; however, it is not disclosed whether quantum dots containing luminescent nanocrystal particles exhibit specific technical effects, and the extent of their technical effects is unclear. Additionally, the OLED light-emitting materials shown in the examples lack wavelength conversion functionality and cannot be reused in light conversion layers utilizing quantum dots.

[0012] Furthermore, when using solvents that are saturated or supersaturated with inactive gases, the following problems occur: when the coating liquid is pumped to the coating machine printhead or nozzle, air bubbles are generated in the flow path of the coating liquid. These air bubbles mix into the coating liquid, resulting in poor coating. Additionally, if used as inkjet ink, there are significant problems such as air bubbles being generated in the printhead of an inkjet printer, leading to poor evacuation.

[0013] Patent document 2 discloses a quantum dot-containing composition that is substantially free of moisture. However, no measured data on the moisture content are provided, and it is unclear what level of moisture is effective.

[0014] Furthermore, there is no description of the IJ method, nor is there any description of the application of the light conversion layer in the color filter (CF) for LCDs.

[0015] In the IJ process, the ink is discharged from the nozzle of the printing head into the atmosphere, exposed to moisture in the air, and remains exposed to the atmosphere after printing. Since the CF substrate has a large area, creating a moisture-free, inactive gas atmosphere near the printhead and on the printing surface of the substrate would significantly increase the equipment price and operating costs. Therefore, there is a need for inks that minimize performance degradation of quantum dots even when exposed to atmospheric moisture.

[0016] Therefore, inks with minimal quantum dot degradation and fewer bubbles generated during ink delivery or within the IJ printhead are required.

[0017] It should be noted that Patent Document 3 discloses a method of degassing oxygen by introducing an inactive gas to expel dissolved oxygen and by degassing under reduced pressure. It also discloses that the luminescence of oxygen-free quantum dot (QD) compositions is less prone to degradation.

[0018] However, when IJ printing inks and their cured films are exposed to the atmosphere, QD (Quality Dioxide) is exposed to atmospheric moisture. In this case, degradation cannot be suppressed by known methods, and a QD composition and its cured product that are beneficial for IJ printing are desired.

[0019] Regarding Patent Documents 2-3, although it is recorded that acrylate monomers and oligomers can be used as photocurable compounds, the monomers actually used in the experiments are only di(meth)acrylates containing long-chain alkylene groups, such as dodecanediol di(meth)acrylate.

[0020] Existing technical documents

[0021] Patent documents

[0022] Patent Document 1: Japanese Patent Publication No. 2016-501430

[0023] Patent Document 2: Specification of U.S. Patent Publication 2014 / 0027673

[0024] Patent Document 3: WO2013 / 122820 Summary of the Invention

[0025] The problem that the invention aims to solve

[0026] The ink composition using luminescent nanocrystal particles and the light conversion layer using the ink composition are unstable to moisture in the atmosphere, so it is necessary to improve their stability.

[0027] The purpose is to provide an ink composition with improved stability to moisture, a method for manufacturing the same, and a light conversion layer and a color filter using the ink composition.

[0028] Methods for solving problems

[0029] The present invention provides the following embodiments respectively.

[0030] According to the ink composition described in 1 below, a photopolymerizable compound with a specific LogP value range is used as the photopolymerizable compound, so that no adverse conditions occur in its cured product, such as improving atmospheric stability.

[0031] 1. An ink composition, characterized in that it contains luminescent nanocrystal particles and a photopolymerizable compound, wherein the LogP value of the aforementioned photopolymerizable compound is greater than or equal to -1.0 and less than or equal to 6.5.

[0032] 2. An ink composition, characterized in that it contains luminescent nanocrystal particles and a photopolymerizable compound,

[0033] The aforementioned photopolymerizable compounds have LogP values ​​ranging from -1.0 to below 6.5.

[0034] The moisture (H2O) content based on the Karl Fischer moisture analyzer is below 90 ppm.

[0035] 3. An ink composition for inkjet printing, characterized in that it contains luminescent nanocrystal particles and a photopolymerizable compound.

[0036] The aforementioned photopolymerizable compounds have LogP values ​​ranging from -1.0 to below 6.5.

[0037] The moisture (H2O) content based on the Karl Fischer moisture analyzer is below 90 ppm.

[0038] 4. The method for manufacturing the ink composition for inkjet printing as described in 3 above is characterized in that the ink composition is subjected to reduced pressure and the dissolved gas is removed.

[0039] 5. The ink composition described in 3 above has a moisture (H2O) content of 20 ppm or less.

[0040] 6. The method for manufacturing the ink composition according to the foregoing 4, characterized in that a photopolymerizable compound that has been dehydrated by incorporating molecular sieves is used.

[0041] 7. The ink composition according to 3 or 5 above, characterized in that it contains a molecular sieve.

[0042] 8. The ink composition for inkjet printing according to any one of 3, 5 or 7 above, wherein the aforementioned photopolymerizable compound is a photoradical polymerizable compound.

[0043] 9. The ink composition for inkjet printing according to any one of 3, 5 or 7 above, wherein the aforementioned photopolymerizable compound is alkali-insoluble.

[0044] 10. The ink composition for inkjet printing according to any one of 3, 5 or 7 above is capable of forming an alkali-insoluble coating film.

[0045] 11. The ink composition for inkjet printing according to any one of 3, 5 or 7 above, having a surface tension of 20 to 40 mN / m.

[0046] 12. The ink composition for inkjet printing as described in any one of 3, 5 or 7 above, having a viscosity of 2 to 20 mPa·s.

[0047] 13. The inkjet ink composition according to any one of 3, 5 or 7 above further contains an organic solvent with a boiling point of 180°C or higher.

[0048] 14. The ink composition for inkjet printing according to any one of 3, 5 or 7 above is for use with a color filter.

[0049] 15. A light conversion layer of a cured product comprising any one of the ink compositions described in 1 to 3 above.

[0050] 16. A light conversion layer, wherein the cured form of the ink composition described in any one of the preceding 1 to 3 is alkali-insoluble.

[0051] 17. A light conversion layer, comprising a plurality of pixels.

[0052] The aforementioned plurality of pixel portions have a cured portion comprising an inkjet ink composition described in any one of the aforementioned 3, 5 or 7.

[0053] 18. The light conversion layer according to any one of claims 15 to 17 above further comprises a light-shielding portion disposed between the aforementioned plurality of pixel portions.

[0054] The aforementioned plurality of pixels have:

[0055] The first pixel portion includes the aforementioned cured material, and contains luminescent nanocrystal particles that absorb light with wavelengths in the range of 420-480 nm and emit light with a emission peak wavelength in the range of 605-665 nm, as the aforementioned luminescent nanocrystal particles.

[0056] The second pixel portion includes the aforementioned solidified material and contains luminescent nanocrystal particles that absorb light with wavelengths in the range of 420 to 480 nm and emit light with a emission peak wavelength in the range of 500 to 560 nm.

[0057] 19. According to any one of the light conversion layers described in 15 to 18 above, the aforementioned plurality of pixel portions further have a third pixel portion having a transmittance of 30% or more for light with a wavelength in the range of 420 to 480 nm.

[0058] 20. A color filter comprising a light conversion layer as described in any one of claims 15 to 19 above.

[0059] Invention Effects

[0060] It can provide ink compositions with improved stability in the atmosphere, methods for manufacturing the same, light conversion layers and color filters using the ink compositions. Attached Figure Description

[0061] [ Figure 1 ] Figure 1 This is a schematic cross-sectional view of a color filter according to one embodiment of the present invention. Detailed Implementation

[0062] The embodiments of the present invention will be described in detail below.

[0063] <Ink Composition>

[0064] The ink composition of the embodiment is characterized by containing luminescent nanocrystal particles and a photopolymerizable compound, wherein the LogP value of the aforementioned photopolymerizable compound is greater than or equal to -1.0 and less than or equal to 6.5.

[0065] One embodiment of the ink composition is, for example, a color filter ink composition used to form the pixel portion of a color filter by means of photolithography, inkjet printing, or the like.

[0066] One embodiment of the ink composition is suitable for use in forming color filter pixels by inkjet printing.

[0067] When using conventional ink compositions to form color filter pixels via, for example, inkjet printing, the light conversion layer deteriorates if exposed to moisture in the atmosphere.

[0068] On the other hand, the ink composition according to this embodiment can improve such problems.

[0069] The following explanation uses a color filter ink composition (color filter inkjet ink) used in inkjet printing as an example.

[0070] [Luminescent nanocrystal particles]

[0071] Luminescent nanocrystals are nanoscale crystals that emit fluorescence or phosphorescence upon absorbing excitation light. For example, they are crystals with a maximum particle size of less than 100 nm as determined by transmission electron microscopy or scanning electron microscopy.

[0072] Luminescent nanocrystal particles can, for example, emit light of a different wavelength (fluorescence or phosphorescence) by absorbing light of a predetermined wavelength. The luminescent nanocrystal particles can be red luminescent nanocrystal particles emitting light (red light) with a peak emission wavelength in the range of 605-665 nm, green luminescent nanocrystal particles emitting light (green light) with a peak emission wavelength in the range of 500-560 nm, or blue luminescent nanocrystal particles emitting light (blue light) with a peak emission wavelength in the range of 420-480 nm. In one embodiment, the ink composition preferably contains at least one of these luminescent nanocrystal particles. Furthermore, the light absorbed by the luminescent nanocrystal particles can be, for example, light with a wavelength in the range of 400 nm or more but less than 500 nm (blue light), or light with a wavelength in the range of 200 nm to 400 nm (ultraviolet light). It should be noted that the peak emission wavelength of the luminescent nanocrystal particles can be confirmed, for example, by using a fluorescence spectrum or phosphorescence spectrum measured using an ultraviolet-visible spectrophotometer.

[0073] The red-luminescent nanocrystal particles preferably have emission peak wavelengths below 665 nm, 663 nm, 660 nm, 658 nm, 655 nm, 653 nm, 651 nm, 650 nm, 647 nm, 645 nm, 643 nm, 640 nm, 637 nm, 635 nm, 632 nm, or 630 nm, and preferably above 628 nm, 625 nm, 623 nm, 620 nm, 615 nm, 610 nm, 607 nm, or 605 nm. These upper and lower limits can be combined arbitrarily. It should be noted that, in the following description, the individually described upper and lower limits can be combined arbitrarily.

[0074] The green luminescent nanocrystal particles preferably have emission peak wavelengths below 560nm, 557nm, 555nm, 550nm, 547nm, 545nm, 543nm, 540nm, 537nm, 535nm, 532nm, or 530nm, and preferably above 528nm, 525nm, 523nm, 520nm, 515nm, 510nm, 507nm, 505nm, 503nm, or 500nm.

[0075] Blue luminescent nanocrystal particles preferably have emission peak wavelengths below 480nm, 477nm, 475nm, 470nm, 467nm, 465nm, 463nm, 460nm, 457nm, 455nm, 452nm, or 450nm, and more preferably above 450nm, 445nm, 440nm, 435nm, 430nm, 428nm, 425nm, 422nm, or 420nm.

[0076] According to the solution of the Schrödinger wave equation in the potential energy trap model, the wavelength (emission color) of the light emitted by luminescent nanocrystal particles depends on the size (e.g., particle size) of the luminescent nanocrystal particles, but also on the band gap they possess. Therefore, by changing the constituent materials and size of the luminescent nanocrystal particles used, the emission color can be selected.

[0077] Luminescent nanocrystal particles can be luminescent nanocrystal particles containing semiconductor materials (luminescent semiconductor nanocrystal particles). Examples of luminescent semiconductor nanocrystal particles include quantum dots (hereinafter also referred to as "QD"), quantum rods, etc. Among these, quantum dots are preferred from the perspective of easy control of the emission spectrum, reducing production costs while ensuring reliability, and improving mass production.

[0078] The luminescent semiconductor nanocrystal particles can consist solely of a core containing a first semiconductor material, or they can have a core containing the first semiconductor material and a shell containing a second semiconductor material different from the first semiconductor material and covering at least a portion of the core. In other words, the structure of the luminescent semiconductor nanocrystal particles can be a structure consisting only of a core (core structure) or a structure consisting of a core and a shell (core / shell structure). Furthermore, in addition to a shell containing the second semiconductor material (first shell), the luminescent semiconductor nanocrystal particles can further have a shell containing a third semiconductor material different from the first and second semiconductor materials and covering at least a portion of the core (second shell). In other words, the structure of the luminescent semiconductor nanocrystal particles can be a structure consisting of a core, a first shell, and a second shell (core / shell / shell structure). The core and shell can each be a mixed crystal containing two or more semiconductor materials (e.g., CdSe+CdS, CIS+ZnS, etc.).

[0079] The luminescent nanocrystal particles preferably contain at least one semiconductor material selected from the group consisting of II-VI semiconductors, III-V semiconductors, I-III-VI semiconductors, IV semiconductors and I-II-IV-VI semiconductors.

[0080] Specific semiconductor materials include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, Cd HgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, CdHgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgS eS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe; GaN, GaP, GaAs, GaSb, AlN, AlP , AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, G aAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb; SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe,

[0081] PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; Si, Ge, SiC, SiGe, AgInSe2, CuGaSe2, CuInS2, CuGaS2, CuInSe2, AgInS2, AgGaSe2, AgGaS2, C, Si and Ge. From the perspective of easy control of the emission spectrum, reducing production costs while ensuring reliability, and improving mass production, the luminescent semiconductor nanocrystal particles preferably include at least one of the following: CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, InP, InAs, InSb, GaP, GaAs, GaSb, AgInS2, AgInSe2, AgInTe2, AgGaS2, AgGaSe2, AgGaTe2, CuInS2, CuInSe2, CuInTe2, CuGaS2, CuGaSe2, CuGaTe2, Si, C, Ge, and Cu2ZnSnS4.

[0082] Examples of red-emitting semiconductor nanocrystal particles include: CdSe nanocrystal particles; rod-shaped CdSe nanocrystal particles; rod-shaped nanocrystal particles with a core-shell structure, where the shell portion is CdS and the inner core is CdSe; rod-shaped nanocrystal particles with a core-shell structure, where the shell portion is CdS and the inner core is ZnSe; nanocrystal particles with a core-shell structure, where the shell portion is CdS and the inner core is CdSe; and nanocrystal particles with a core-shell structure, where the shell portion is CdS and the inner core is CdSe. Nanocrystalline particles consisting of CdS with a ZnSe core on the inner side; mixed crystal nanoparticles of CdSe and ZnS; rod-shaped mixed crystal nanoparticles of CdSe and ZnS; nanocrystalline particles of InP; rod-shaped mixed crystal nanoparticles of InP; mixed crystal nanoparticles of CdSe and CdS; rod-shaped mixed crystal nanoparticles of CdSe and CdS; mixed crystal nanoparticles of ZnSe and CdS; rod-shaped mixed crystal nanoparticles of ZnSe and CdS, etc.

[0083] Examples of green luminescent semiconductor nanocrystal particles include CdSe nanocrystal particles, rod-shaped CdSe nanocrystal particles, mixed CdSe and ZnS nanocrystal particles, and mixed CdSe and ZnS rod-shaped nanocrystal particles.

[0084] Examples of blue luminescent semiconductor nanocrystal particles include: ZnSe nanocrystal particles; rod-shaped ZnSe nanocrystal particles; ZnS nanocrystal particles; rod-shaped ZnS nanocrystal particles; nanocrystal particles with a core-shell structure, where the shell is ZnSe and the inner core is ZnS; rod-shaped nanocrystal particles with a core-shell structure, where the shell is ZnSe and the inner core is ZnS; CdS nanocrystal particles; rod-shaped CdS nanocrystal particles, etc. Regarding semiconductor nanocrystal particles, by changing their average particle size while maintaining the same chemical composition, the color emitted by the particle can be changed to red or green. Furthermore, the semiconductor nanocrystal particles themselves preferably use substances with extremely low adverse effects on the human body, etc. When using semiconductor nanocrystal particles containing cadmium, selenium, etc., as luminescent nanocrystal particles, it is preferable to select semiconductor nanocrystal particles that contain as few of the aforementioned elements (cadmium, selenium, etc.) as possible, or to combine them with other luminescent nanocrystal particles in a manner that minimizes the presence of these elements.

[0085] The shape of the luminescent nanocrystal particles is not particularly limited; they can be any geometric shape or any irregular shape. Examples of the shapes of luminescent nanocrystal particles include spherical, ellipsoidal, pyramidal, disk-shaped, dendritic, network-like, and rod-shaped particles. However, to further improve the uniformity and flowability of the ink composition, particles with low directionality (e.g., spherical, tetrahedral, etc.) are preferred as the particle shape.

[0086] Regarding the average particle size (volume average diameter) of the luminescent nanocrystal particles, considering the ease of obtaining the desired wavelength of emission and excellent dispersibility and storage stability, it can be 1 nm or more, 1.5 nm or more, or 2 nm or more. Considering the ease of obtaining the desired emission wavelength, it can be less than 40 nm, 30 nm or less, or 20 nm or less. The average particle size (volume average diameter) of the luminescent nanocrystal particles can be obtained by measuring and calculating the volume average diameter using a transmission electron microscope or a scanning electron microscope.

[0087] From the viewpoint of dispersion stability, luminescent nanocrystal particles preferably have organic ligands on their surface. Organic ligands can, for example, coordinate and bind to the surface of the luminescent nanocrystal particles. In other words, the surface of the luminescent nanocrystal particles can be passivated with organic ligands. Additionally, the luminescent nanocrystal particles can have a polymeric dispersant on their surface. In one embodiment, for example, the polymeric dispersant can be bound to the surface of the luminescent nanocrystal particles by removing the organic ligands from the aforementioned luminescent nanocrystal particles and exchanging the organic ligands with the polymeric dispersant. However, from the viewpoint of dispersion stability when formulating inkjet inks, it is preferable to combine the luminescent nanocrystal particles, which maintain the state of having coordinated organic ligands, with a polymeric dispersant.

[0088] Examples of organic ligands include TOP (trioctylphosphine), TOPO (trioctylphosphine oxide), oleic acid, oleylamine, octylamine, trioctylamine, hexadecylamine, octylthiol, dodecylthiol, hexylphosphonic acid (HPA), tetradecylphosphonic acid (TDPA), and octylphosphonic acid (OPA).

[0089] As luminescent nanocrystal particles, these can be substances dispersed in colloidal form in organic solvents, photopolymerizable compounds, etc. The surface of the luminescent nanocrystal particles dispersed in organic solvents is preferably passivated with the aforementioned organic ligands. Examples of organic solvents include cyclohexane, hexane, heptane, chloroform, toluene, octane, chlorobenzene, tetrahydronaphthalene, diphenyl ether, propylene glycol monomethyl ether acetate, butyl carbitol acetate, or mixtures thereof.

[0090] Commercially available products can be used as luminescent nanocrystal particles. Examples of commercially available luminescent nanocrystal particles include indium phosphide / zinc sulfide, D-dots, CuInS / ZnS from NN-LABS, and InP / ZnS from Aldrich.

[0091] Regarding the content of luminescent nanocrystal particles, from the perspective of better light leakage reduction, based on the mass of the non-volatile components of the ink composition, it can be 5% by mass or more, or 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 30% by mass or more, or 40% by mass or more. Regarding the content of luminescent nanocrystal particles, from the perspective of excellent emission stability, based on the mass of the non-volatile components of the ink composition, it can be 70% by mass or less, or 60% by mass or less, or 55% by mass or less, or 50% by mass or less. It should be noted that in this specification, the "mass of the non-volatile components of the ink composition" refers to the total mass of the ink composition minus the mass of the organic solvent when the ink composition contains organic solvents; when the ink composition does not contain organic solvents, it refers to the total mass of the ink composition.

[0092] Furthermore, luminescent nanocrystal particles possess high reactivity due to their surface atoms, which can serve as coordination sites. This high reactivity, combined with their larger surface area than typical pigments, makes them prone to aggregation. Since luminescence occurs due to quantum size effects, aggregation leads to extinction, resulting in a decrease in fluorescence quantum yield, brightness, and color reproducibility. In contrast, in this embodiment, the ink composition contains a polymeric dispersant, thus preventing aggregation of the luminescent nanocrystal particles. Therefore, in this embodiment, the content of luminescent nanocrystal particles can be within the aforementioned range.

[0093] [Light-scattering particles]

[0094] One embodiment of the ink composition may contain light-scattering particles. When a color filter pixel (hereinafter referred to simply as "pixel") is formed using an ink composition employing luminescent nanocrystal particles, light from the light source sometimes leaks out of the pixel without being absorbed by the luminescent nanocrystal particles. Such light leakage reduces the color reproducibility of the pixel; therefore, when using the aforementioned pixel as a light conversion layer, it is preferable to minimize this light leakage as much as possible. The aforementioned light-scattering particles are suitable for preventing light leakage from the pixel. Light-scattering particles are, for example, optically inactive inorganic microparticles. Light-scattering particles are capable of scattering light emitted from a light source that illuminates the color filter pixel.

[0095] Materials constituting light-scattering particles may include, for example, single metals such as tungsten, zirconium, titanium, platinum, bismuth, rhodium, palladium, silver, tin, platinum, and gold; metal oxides such as silicon dioxide, barium sulfate, barium carbonate, calcium carbonate, talc, titanium dioxide, clay, kaolin, barium sulfate, barium carbonate, calcium carbonate, aluminum oxide, titanium dioxide, magnesium oxide, barium oxide, aluminum oxide, bismuth oxide, zirconium oxide, and zinc oxide; metal carbonates such as magnesium carbonate, barium carbonate, bismuth subcarbonate, and calcium carbonate; metal hydroxides such as aluminum hydroxide; composite oxides such as barium zirconate, calcium zirconate, calcium titanate, barium titanate, and strontium titanate; and metal salts such as bismuth subnitrate. From the viewpoint of achieving a superior reduction in light leakage, the light-scattering particles preferably include at least one element selected from the group consisting of titanium dioxide, aluminum oxide, zirconium oxide, zinc oxide, calcium carbonate, barium sulfate, and silicon dioxide, and more preferably at least one element selected from the group consisting of titanium dioxide, barium sulfate, and calcium carbonate.

[0096] The shape of light-scattering particles can be spherical, filamentous, or irregular. However, as light-scattering particles, in order to further improve the uniformity, flowability, and light scattering properties of the ink composition, particles with low directionality (such as spherical, tetrahedral, etc.) are preferred as particle shape.

[0097] Regarding the average particle size (volume average diameter) of the light-scattering particles in the ink composition, from the viewpoint of achieving better light leakage reduction, it can be 0.05 μm or more, or 0.2 μm or more, or 0.3 μm or more. Regarding the average particle size (volume average diameter) of the light-scattering particles in the ink composition, from the viewpoint of achieving excellent discharge stability, it can be 1.0 μm or less, or 0.6 μm or less, or 0.4 μm or less. Regarding the average particle size (volume average diameter) of the light-scattering particles in the ink composition, it can be 0.05~1.0 μm, 0.05~0.6 μm, 0.05~0.4 μm, 0.2~1.0 μm, 0.2~0.6 μm, 0.2~0.4 μm, 0.3~1.0 μm, 0.3~0.6 μm, or 0.3~0.4 μm. From the viewpoint of easily obtaining such an average particle size (volume average diameter), the average particle size (volume average diameter) of the light-scattering particles used can be greater than 50 nm or less than 1000 nm. The average particle size (volume average diameter) of the light-scattering particles can be obtained by measuring and calculating the volume average diameter using a dynamic light-scattering nanoparticle size distribution meter. Alternatively, the average particle size (volume average diameter) of the light-scattering particles used can be obtained, for example, by measuring the particle size of each particle using a transmission electron microscope or a scanning electron microscope and calculating the volume average diameter.

[0098] Regarding the content of light-scattering particles, from the viewpoint of achieving a superior light leakage reduction effect, based on the mass of the non-volatile components of the ink composition, it can be 0.1% by mass or more, or 1% by mass or more, or 5% by mass or more, or 7% by mass or more, or 10% by mass or more, or 12% by mass or more. Regarding the content of light-scattering particles, from the viewpoints of achieving a superior light leakage reduction effect and excellent emission stability, based on the mass of the non-volatile components of the ink composition, it can be 60% by mass or less, or 50% by mass or less, or 40% by mass or less, or 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less. In this embodiment, since the ink composition contains a polymeric dispersant, the light-scattering particles can be well dispersed even when the content of light-scattering particles is set within the above-mentioned ranges.

[0099] The mass ratio (light-scattering particles / luminescent nanocrystal particles) of light-scattering particles to luminescent nanocrystal particles is 0.1 to 5.0. From the perspective of achieving better light leakage reduction, the mass ratio (light-scattering particles / luminescent nanocrystal particles) can be 0.2 or higher, or 0.5 or higher. From the perspective of achieving better light leakage reduction and better continuous ejection during inkjet printing, the mass ratio (light-scattering particles / luminescent nanocrystal particles) can be 2.0 or lower, or 1.5 or lower. The mass ratio (light-scattering particles / luminescent nanocrystal particles) can be 0.1 to 2.0, 0.1 to 1.5, 0.2 to 5.0, 0.2 to 2.0, 0.2 to 1.5, 0.5 to 5.0, 0.5 to 2.0, or 0.5 to 1.5. It should be noted that the light leakage reduction achieved using light-scattering particles is considered to be based on the following mechanism. In other words, it is believed that when light-scattering particles are absent, the backlight travels almost directly through the pixel, with little chance of being absorbed by the luminescent nanocrystal particles. On the other hand, it is believed that if light-scattering particles are present in the same pixel as the luminescent nanocrystal particles, the backlight is scattered omnidirectionally within that pixel, allowing the luminescent nanocrystal particles to receive the light. Therefore, even using the same backlight, the amount of light absorbed in the pixel increases. The result is that it is believed that light leakage can be prevented through this mechanism.

[0100] [Polymer Dispersant]

[0101] In one embodiment of the ink composition, a polymeric dispersant is preferably included. The polymeric dispersant enables the light-scattering particles to be more uniformly dispersed in the ink.

[0102] In this invention, the polymeric dispersant is a polymeric compound having a weight-average molecular weight of 750 or higher and possessing functional groups that have an affinity for light-scattering particles, thus dispersing the light-scattering particles. Regarding the polymeric dispersant, through its functional groups that have an affinity for light-scattering particles, the polymeric dispersant adsorbs onto the light-scattering particles. Utilizing the electrostatic repulsion and / or steric repulsion between the polymeric dispersants, the light-scattering particles are dispersed in the ink composition. Preferably, the polymeric dispersant binds to the surface of the light-scattering particles and adsorbs onto them, but it can also bind to the surface of luminescent nanocrystal particles and adsorb onto them, or it can remain free in the ink composition.

[0103] Functional groups that have an affinity for light-scattering particles can be categorized into acidic, basic, and nonionic functional groups. Acidic functional groups have dissociable protons that can be neutralized by bases such as amines and hydroxide ions, while basic functional groups can be neutralized by acids such as organic and inorganic acids.

[0104] As acidic functional groups, examples include carboxyl (-COOH), sulfonyl (-SO3H), sulfate (-OSO3H), phosphonic acid (-PO(OH)3), phosphate (-OPO(OH)3), hypophosphonic acid (-PO(OH)-), and mercapto (-SH).

[0105] As basic functional groups, examples include primary amino, secondary amino and tertiary amino, ammonium, imino, and nitrogen-containing heterocyclic groups such as pyridine, pyrimidine, pyrazine, imidazole, and triazole.

[0106] As nonionic functional groups, examples include hydroxyl, ether, thioether, sulfinyl (-SO-), sulfonyl (-SO2-), carbonyl, formyl, ester, carbonate, amide, carbamoyl, urea, thioamide, thiourea, aminosulfonyl, cyano, alkenyl, alkynyl, phosphine oxy, and phosphine sulfide.

[0107] From the perspectives of the dispersion stability of light-scattering particles, the difficulty in causing side effects such as sedimentation of luminescent nanocrystal particles, the ease of synthesis of polymeric dispersants, and the stability of functional groups, carboxyl, sulfonyl, phosphonic acid, and phosphate groups are preferred as acidic functional groups, and amino groups are preferred as basic functional groups. Among these, carboxyl, phosphonic acid, and amino groups are more preferred, and amino groups are most preferred.

[0108] Polymer dispersants with acidic functional groups have an acid value. The acid value of the polymer dispersant with acidic functional groups is preferably 1 to 150 mg KOH / g when converted to solid content. If the acid value is 1 or higher, sufficient dispersion of light-scattering particles is easily obtained; if the acid value is 150 or lower, the preservation stability of the pixel portion (the cured form of the ink composition) is difficult to reduce.

[0109] Furthermore, polymeric dispersants with basic functional groups have an amine value. The amine value of polymeric dispersants with basic functional groups is preferably 1-200 mg KOH / g when converted to solid content. If the amine value is 1 or higher, sufficient dispersion of light-scattering particles is easily obtained; if the amine value is 200 or lower, the preservation stability of the pixel portion (the cured form of the ink composition) is difficult to reduce.

[0110] Polymer dispersants can be polymers of a single monomer (homogeneities) or copolymers of multiple monomers (copolymers). Furthermore, polymer dispersants can be any of the following: random copolymers, block copolymers, or graft copolymers. When a polymer dispersant is a graft copolymer, it can be a comb-shaped graft copolymer or a star-shaped graft copolymer. Examples of polymer dispersants include acrylic resins, polyester resins, polyurethane resins, polyamide resins, polyethers, phenolic resins, silicone resins, polyurea resins, amino resins, polyamines such as polyethyleneimine and polyacrylamide, epoxy resins, and polyimides.

[0111] As the aforementioned polymeric dispersant, commercially available products can also be used. These include AJISPER PB series from Ajinomoto Fine Chemicals Co., Ltd., DISPERBYK series and BYK- series from BYK Corporation, and Efka series from BASF Corporation.

[0112] As commercially available products, for example, "DISPERBYK-130", "DISPERBYK-161", "DISPERBYK-162", "DISPERBYK-163", "DISPERBYK-164", "DISPERBYK-166", "DISPERBYK-167", "DISPERBYK-168", "DISPERBYK-170", "DISPERBYK-171", "DISPERBYK-174", "DISPERBYK-180", "DISPERBYK-182", "DISPERBYK-183", "DISPERBYK-184", "DISPERBYK-185", "DISPERBYK-2000", "DISPERBYK-2001", "DISPERBYK-2008", "DISPERBYK-2009", "DISPERBYK-2020", "DISPERBYK-2022", "DISPERBYK-2025", "DISPERBYK-2050", "DISPERBYK-2070", "DISPERBYK-2096", "DISPERBYK-2150", "DISPERBYK-2155", "DISPERBYK-2163", "DISPERBYK-2164", "BYK-LPN21116" and "BYK-LPN6919" manufactured by BYK Co., Ltd.; "EFKA4010", "EFKA4015", "EFKA4046", "EFKA4047", "EFKA4061", "EFKA4080", "EFKA4300", "EFKA4310", "EFKA4320", "EFKA4330", "EFKA4340", "EFKA4560", "EFKA4585", "EFKA5207", "EFKA1501", "EFKA1502", "EFKA1503" and "EFKA PX-4701" manufactured by BASF SE;"Solsperse 3000", "Solsperse 9000", "Solsperse 13240", "Solsperse 13650", "Solsperse 13940", "Solsperse 11200", "Solsperse 13940", "Solsperse 16000", "Solsperse 17000", "Solsperse 18000", "Solsperse 20000", "Solsperse 21000", "Solsperse 24000", "Solsperse 26000", "Solsperse 27000", "Solsperse 28000", "Solsperse 32000", "Solsperse 32500", "Solsperse 32550", "Solsperse 32600", "Solsperse 33000", "Solsperse 34750", "Solsperse 35100", "Solsperse 35200", "Solsperse 36000", "Solsperse 37500", "Solsperse 38500", "Solsperse 39000", "Solsperse 41000", "Solsperse 54000", "Solsperse 71000" and "Solsperse 76500" manufactured by Lubrizol Corporation; "AJISPER PB821", "AJISPER PB822", "AJISPER PB881", "PN411" and "PA111" manufactured by Ajinomoto Fine-Techno Co., Inc.; "TEGO Dispers 650", "TEGO Dispers 660C", "TEGO Dispers 662C", "TEGO Dispers 670", "TEGO Dispers 685", "TEGO Dispers 700", "TEGO Dispers 710" and "TEGO Dispers 760W" manufactured by Evonik; "DISPARLON DA-703-50", "DA-705" and "DA-725" manufactured by Kusumoto Chemicals, Ltd., and the like.;

[0113] In addition to commercially available products as described above, substances synthesized by copolymerizing cationic monomers with basic groups and / or anionic monomers with acidic groups, monomers with hydrophobic groups, and other monomers as needed (nonionic monomers, monomers with hydrophilic groups, etc.) can also be used as polymeric dispersants. Details regarding cationic monomers, anionic monomers, monomers with hydrophobic groups, and other monomers can be found in paragraphs 0034 to 0036 of Japanese Patent Application Publication No. 2004-250502.

[0114] In addition, suitable examples include, for instance, compounds obtained by reacting polyalkylimides with polyester compounds as described in Japanese Patent Application Publication No. 54-37082 and Japanese Patent Application Publication No. 61-174939; compounds obtained by modifying the amino groups of the side chains of polyacrylamide with polyester as described in Japanese Patent Application Publication No. 9-169821; graft polymers with polyester-type macromonomers as copolymerizing components as described in Japanese Patent Application Publication No. 9-171253; and polyurethanes formed by the addition of polyester polyols as described in Japanese Patent Application Publication No. 60-166318.

[0115] Regarding the weight-average molecular weight of the polymeric dispersant, from the viewpoint of effectively dispersing light-scattering particles and further improving the light leakage reduction effect, it can be 750 or higher, 1000 or higher, 2000 or higher, or 3000 or higher. Regarding the weight-average molecular weight of the polymeric dispersant, from the viewpoint of effectively dispersing light-scattering particles, further improving the light leakage reduction effect, and setting the viscosity of the inkjet ink to a viscosity suitable for discharge and stable discharge, it can be 100,000 or lower, 50,000 or lower, or 30,000 or lower. In this specification, the weight-average molecular weight refers to the weight-average molecular weight converted from polystyrene as determined by GPC (Gel Permeation Chromatography).

[0116] Regarding the content of the polymeric dispersant, from the viewpoint of the dispersibility of light-scattering particles, it can be 0.5 parts by mass or more, or 2 parts by mass or more, or 5 parts by mass or more, relative to 100 parts by mass of light-scattering particles. Regarding the content of the polymeric dispersant, from the viewpoint of the hydrothermal stability of the pixel portion (the cured ink composition), it can be 50 parts by mass or less, or 30 parts by mass or less, or 10 parts by mass or less, relative to 100 parts by mass of light-scattering particles.

[0117] [Photopolymerizable compounds]

[0118] The photopolymerizable compounds of this embodiment are photoradical polymers or photocationic polymers that polymerize upon light irradiation. They can be suitably used with photopolymerization initiators. Photoradical polymers are used with photoradical polymerization initiators, and photocationic polymers are used with photocationic polymerization initiators. In other words, the ink composition may contain photopolymerizable components comprising photopolymerizable compounds and photopolymerization initiators, or it may contain photoradical polymerizable components comprising photoradical polymers and photoradical polymerization initiators, or it may contain photocationic polymerizable components comprising photocationic polymers and photocationic polymerization initiators. Photoradical polymers and photocationic polymers can be used together, or compounds possessing both photoradical and photocationic polymerizable properties can be used, or photoradical polymerization initiators and photocationic polymerization initiators can be used together. One photopolymerizable compound can be used alone, or two or more can be used together.

[0119] Examples of photoradical polymerizable compounds include (meth)acrylate compounds. These (meth)acrylate compounds can be monofunctional (meth)acrylates having one (meth)acryloyl group, or polyfunctional (meth)acrylates having multiple (meth)acryloyl groups. From the viewpoints of excellent flowability when used in ink production, superior discharge stability, and the ability to suppress the reduction in smoothness caused by curing shrinkage during filter manufacturing, it is preferable to use a combination of monofunctional and polyfunctional (meth)acrylates. It should be noted that in this specification, (meth)acrylate means "acrylate" and its corresponding "methacrylate." The same applies to the expression "(meth)acryloyl group."

[0120] Examples of monofunctional (meth)acrylates include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, nonyl methacrylate, dodecyl methacrylate, hexadecyl methacrylate, octadecyl methacrylate, cyclohexyl methacrylate, methoxyethyl methacrylate, butoxyethyl methacrylate, phenoxyethyl methacrylate, nonylphenoxyethyl methacrylate, and glycidyl methacrylate. Dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, dicyclopentenyl methacrylate, dicyclopentenoxyethyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, tetrahydrofurfuryl methacrylate, 2-hydroxyethyl methacrylate, benzyl methacrylate, phenyl benzyl methacrylate, mono(2-acryloyloxyethyl)succinate, N-[2-(acryloyloxy)ethyl]phthalimide, N-[2-(acryloyloxy)ethyl]tetrahydrophthalimide, etc.

[0121] Polyfunctional (meth)acrylates can be difunctional (meth)acrylates, trifunctional (meth)acrylates, tetrafunctional (meth)acrylates, pentafunctional (meth)acrylates, hexafunctional (meth)acrylates, etc. For example, they can be di(meth)acrylates obtained by replacing two hydroxyl groups of a diol compound with (meth)acryloyloxy groups, or di or tri(meth)acrylates obtained by replacing two or three hydroxyl groups of a triol compound with (meth)acryloyloxy groups, etc.

[0122] Specific examples of difunctional (meth)acrylates include 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, 1,5-pentanediol dimethacrylate, 3-methyl-1,5-pentanediol dimethacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol dimethacrylate, 1,8-octanediol dimethacrylate, 1,9-nonanediol dimethacrylate, tricyclodecanediethanol dimethacrylate, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, propylene glycol dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, polypropylene glycol dimethacrylate, neopentyl glycol hydroxypentyl acrylate dimethacrylate, and tripropylene glycol dimethacrylate. Di(meth)acrylates are derived from the following: di(2-hydroxyethyl)isocyanurate, which has two hydroxyl groups replaced by (meth)acryloyloxy groups; di(meth)acrylates are derived from the following: diols obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol, which have two hydroxyl groups replaced by (meth)acryloyloxy groups; di(meth)acrylates are derived from the following: diols obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A, which have two hydroxyl groups replaced by (meth)acryloyloxy groups; di(meth)acrylates are derived from the following: diols obtained by adding 3 or more moles of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane, which have two hydroxyl groups replaced by (meth)acryloyloxy groups; di(meth)acrylates are derived from the following: diols obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A, which have two hydroxyl groups replaced by (meth)acryloyloxy groups.

[0123] Specific examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, glycerol triacrylate, pentaerythritol tri(meth)acrylate, and tri(meth)acrylates formed by replacing the three hydroxyl groups of a triol obtained by adding 3 or more moles of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane with (meth)acryloyloxy groups.

[0124] As a specific example of a 4-functional (meth)acrylate, pentaerythritol tetra(meth)acrylate can be cited.

[0125] As a specific example of a 5-functional (meth)acrylate, dipentaerythritol penta(meth)acrylate can be cited.

[0126] As a specific example of a hexafunctional (meth)acrylate, dipentaerythritol hexa(meth)acrylate can be cited.

[0127] Polyfunctional (meth)acrylates can be poly(meth)acrylates formed by replacing multiple hydroxyl groups of dipentaerythritol hexa(meth)acrylate with (meth)acryloyloxy groups.

[0128] (Meth)acrylate compounds can be ethylene oxide-modified phosphate (meth)acrylates with phosphate groups, ethylene oxide-modified alkyl phosphate (meth)acrylates, etc.

[0129] Examples of photocationically polymerizable compounds include epoxides, oxetanes, and vinyl ethers.

[0130] Examples of epoxy compounds include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, phenolic varnish type epoxy compounds, trimethylolpropane polyglycidyl ether, neopentyl glycol diglycidyl ether and other aliphatic epoxy compounds, 1,2-epoxy-4-vinylcyclohexane, 1-methyl-4-(2-methylepoxyethoxy)-7-oxabicyclo[4.1.0]heptane and other alicyclic epoxy compounds.

[0131] Commercially available epoxy compounds can also be used. Examples of commercially available epoxy compounds include "CELLOXIDE 2000", "CELLOXIDE 3000", and "CELLOXIDE 4000" manufactured by Daicel Chemical Industries, Ltd.

[0132] Examples of cationicly polymerizable oxetane compounds include 2-ethylhexyloxetane, 3-hydroxymethyl-3-methyloxetane, 3-hydroxymethyl-3-ethyloxetane, 3-hydroxymethyl-3-propyloxetane, 3-hydroxymethyl-3-n-butyloxetane, 3-hydroxymethyl-3-phenyloxetane, 3-hydroxymethyl-3-benzyloxetane, 3-hydroxyethyl-3-methyloxetane, 3-hydroxyethyl-3-ethyloxetane, 3-hydroxyethyl-3-propyloxetane, 3-hydroxyethyl-3-phenyloxetane, 3-hydroxypropyl-3-methyloxetane, 3-hydroxypropyl-3-ethyloxetane, 3-hydroxypropyl-3-phenyloxetane, 3-hydroxypropyl-3-methyloxetane, 3-hydroxypropyl-3-ethyloxetane, 3-hydroxypropyl-3-propyloxetane, 3-hydroxypropyl-3-phenyloxetane, and 3-hydroxybutyl-3-methyloxetane.

[0133] As an oxacyclobutane compound, commercially available products can also be used. Commercially available oxetane compounds include, for example, the ARON OXETANE series (“OXT-101”, “OXT-212”, “OXT-121”, “OXT-221”, etc.) manufactured by Toa Synthetic Co., Ltd.; “CELLOXIDE 2021”, “CELLOXIDE 2021A”, “CELLOXIDE2021P”, “CELLOXIDE 2080”, “CELLOXIDE 2081”, “CELLOXIDE 2083”, “CELLOXIDE 2085”, “EPOLEAD GT300”, “EPOLEAD GT301”, “EPOLEAD GT302”, “EPOLEAD GT400”, “EPOLEAD GT401” and “EPOLEAD GT403” manufactured by Daicel Chemical Co., Ltd.; and “cyracure UVR-6105”, “cyracureUVR-6107”, “cyracure…” manufactured by Dow Chemical Japan Co., Ltd. UVR-6110, Cyracure UVR-6128, ERL4289, and ERL4299, etc., can also be used. In addition, well-known oxetane compounds (such as the oxetane compounds described in Japanese Patent Application Publication No. 2009-40830, etc.) can also be used.

[0134] Examples of vinyl ether compounds include 2-hydroxyethyl vinyl ether, triethylene glycol vinyl monoether, tetraethylene glycol divinyl ether, and trimethylolpropane trivinyl ether.

[0135] Alternatively, the photopolymerizable compound described in paragraphs 0042 to 0049 of Japanese Patent Application Publication No. 2013-182215 may also be used as the photopolymerizable compound in this embodiment.

[0136] [LogP value]

[0137] The most significant feature of the ink composition in this invention is the use of photopolymerizable compounds within a specific LogP value range. For example, a photopolymerizable compound within this specific LogP value range can be selected from the photopolymerizable compounds exemplified above as an essential component. By using photopolymerizable compounds within such a specific LogP value range, this invention enables the cured product to be a cured product less prone to adverse conditions. In this invention, the LogP value represents the logarithmic value of the partition coefficient of the photopolymerizable compound, 1-octanol / water, calculated using the method described in the *Journal of Pharmaceutical Sciences*, p. 83, Vol. 84, No. 1, 1995 (by William M. Meylan and Philip H. Howard). The logP value is generally used as a numerical value for the relative evaluation of the hydrophilicity and hydrophobicity of organic compounds.

[0138] For example, it can be calculated as follows.

[0139] 1,4-Butanediol diacetate 1.39

[0140] Tetrahydronaphthalene 3.27

[0141] LDO 1.35

[0142] OXT-221 2.02

[0143] Ethylene glycol - 1.61

[0144] Lauryl methacrylate 6.68

[0145] It should be noted that the logarithm of the partition coefficient of 1-octanol / water can also be measured based on JIS Z 7260-117, but the above literature shows that the value obtained by the above calculation method shows a very good correlation with most of the measured results.

[0146] In the ink composition of the present invention, the photopolymerizable compound in the inkjet ink composition has a LogP value of -1.0 to 6.5 or less. If necessary, a photopolymerizable compound with a LogP value outside this range may also be included without impairing the technical effect of the present invention.

[0147] In terms of suppressing the degradation of luminescent nanocrystals due to moisture, the LogP value of the photopolymerizable compound can be 5.0 or less, 4.0 or less, 3.0 or less, or 2.0 or less. Furthermore, from the viewpoint of suppressing the water absorption of the ink composition containing luminescent nanocrystals, it can be -0.5 or more, 0.0 or more, or 1.0 or more.

[0148] When the ink contains a photopolymerizable compound whose LogP value is outside the range of -1.0 to 6.5, the photopolymerizable compound in the ink can be 30% by mass or less, 20% by mass or less, 10% by mass or less, 5% by mass or less, or 2% by mass or less, in order to suppress the deterioration of luminescent nanocrystals due to oxygen and moisture in the atmosphere.

[0149] From the perspective of easily setting the LogP value to the above range, the molecular weight of photopolymerizable compounds can be below 1000, below 700, below 500, below 300, or below 200.

[0150] In the ink composition of this embodiment, when the curable component is composed only of a photopolymerizable compound or is composed mainly of such a compound, it is more preferable to use a multifunctional photopolymerizable compound having two or more polymerizable functional groups per molecule as an essential component, since it can further improve the durability (strength, heat resistance, etc.) of the cured product.

[0151] From the viewpoint of easily obtaining a color filter pixel section with excellent reliability, the photopolymerizable compound can be alkali-insoluble. In this specification, "alkali-insoluble" means that, based on the total mass of the photopolymerizable compound, its solubility relative to a 1% by mass aqueous solution of potassium hydroxide at 25°C is 30% by mass or less. Preferably, the solubility of the photopolymerizable compound is 10% by mass or less, more preferably 3% by mass or less.

[0152] Regarding the content of photopolymerizable compounds, considering the viewpoints of easily obtaining suitable viscosity as inkjet ink, improving the curability of the ink composition, and enhancing the solvent resistance and abrasion resistance of the pixel portion (the cured ink composition), the content can be 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the mass of the non-volatile components of the ink composition. Regarding the content of photopolymerizable compounds, considering the viewpoints of easily obtaining suitable viscosity as inkjet ink and obtaining superior optical properties (light leakage), the content can be 90% by mass or less, 80% by mass or less, 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the mass of the non-volatile components of the ink composition.

[0153] From the viewpoint of excellent stability of the pixel portion (cured ink composition) (e.g., excellent resistance to degradation over time, high-temperature storage stability, and humid heat storage stability), photopolymerizable compounds may have crosslinking groups. Crosslinking groups are functional groups that react with other crosslinking groups using heat or active energy rays (e.g., ultraviolet light), and examples include epoxy groups, oxetyl groups, vinyl groups, acryloyl groups, acryloyloxy groups, vinyl ether groups, etc.

[0154] [Photoradical polymerization initiator]

[0155] Molecularly cleaved or hydrogen-extracting photoradical polymerization initiators are suitable as photoradical polymerization initiators.

[0156] As molecularly cleaving photoradical polymerization initiators, suitable options include benzoin isobutyl ether, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide. Other molecularly cleaving photoradical polymerization initiators besides these can also be used in combination with 1-hydroxycyclohexylphenyl ketone, benzoin ethyl ether, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one.

[0157] Examples of hydrogen-extracting photoradical polymerization initiators include benzophenone, 4-phenylbenzophenone, isophthalobenzophenone, and 4-benzoyl-4'-methyl-diphenyl sulfide. Molecular cleavage-type photoradical polymerization initiators and hydrogen-extracting photoradical polymerization initiators can also be used in combination.

[0158] [Photocationic Polymerization Initiator]

[0159] Examples of photocationic polymerization initiators include polyaryl sulfonates such as triphenylsulfonium hexafluoroantimonate and triphenylsulfonium hexafluorophosphonate; and diphenyliodide. Hexafluoroantimonate, p-nonylphenyl iodine Polyaryl iodine such as hexafluoroantimonate Salt, etc.

[0160] Commercially available products can also be used as photocationic polymerization initiators. Examples of commercially available products include sulfonium salt-based photocationic polymerization initiators such as "CPI-100P" manufactured by San-Apro, acylphosphine oxide compounds such as "Lucirin TPO" manufactured by BASF, and "Irgacure 907", "Irgacure 819", "Irgacure 379EG", "Irgacure 184", and "Irgacure PAG290" manufactured by BASF.

[0161] Regarding the content of the photopolymerization initiator, from the viewpoint of the curability of the ink composition, it can be 0.1 parts by mass or more, 0.5 parts by mass or more, or 1 part by mass or more, relative to 100 parts by mass of the photopolymerizable compound. Regarding the content of the photopolymerization initiator, from the viewpoint of the time-dependent stability of the pixel portion (the cured ink composition), it can be 40 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less, relative to 100 parts by mass of the photopolymerizable compound.

[0162] Regarding the content of photopolymerizable compounds in the ink composition, considering the viewpoints of easily obtaining suitable viscosity as an inkjet ink, improving the curability of the ink composition, and enhancing the solvent resistance and abrasion resistance of the pixel portion (the cured product of the ink composition), the content can be 3% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the mass of the non-volatile components in the ink composition. Furthermore, regarding the content of photopolymerizable compounds, considering the viewpoints of ensuring that the viscosity of the inkjet ink does not become excessively high and that the thickness of the pixel portion does not become excessively thick for the light conversion function, the content can be 80% by mass or less, 60% by mass or less, or 50% by mass or less, based on the mass of the non-volatile components in the ink composition.

[0163] The ink composition of the present invention is a photocurable ink composition using photopolymerizable compounds, and therefore can suppress the deterioration of luminescent nanocrystal particles caused, for example, by thermal curing at high temperatures.

[0164] The ink composition of this embodiment can be used in inks that are commonly used in the manufacturing methods of color filters. However, in terms of not wasting expensive materials such as luminescent nanocrystal particles and solvents, and being able to form the color filter pixel part (light conversion layer) only in the necessary amount at the necessary locations, it is preferable to use it in a way that is more suitable for inkjet printing than for photolithography.

[0165] Regarding the viscosity of the ink composition, from the viewpoint of ejection stability during inkjet printing, it can be 2 mPa·s or higher, 5 mPa·s or higher, or 7 mPa·s or higher. The viscosity of the ink composition can be 20 mPa·s or lower, 15 mPa·s or lower, or 12 mPa·s or lower. When the viscosity of the ink composition is 2 mPa·s or higher, the meniscus shape of the ink composition is stable at the tip of the ink ejection orifice of the ejection nozzle, thus making it easier to control the ejection of the ink composition (e.g., control of ejection volume and ejection timing). On the other hand, when the viscosity is 20 mPa·s or lower, the ink composition can be ejected smoothly from the ink ejection orifice. The viscosity of the ink composition can be 2~20 mPa·s, 2~15 mPa·s, 2~12 mPa·s, 5~20 mPa·s, 5~15 mPa·s, 2~20 mPa·s, 7~15 mPa·s, 7~12 mPa·s, s, or 7~12 mPa·s. The viscosity of the ink composition is measured, for example, using an E-type viscometer.

[0166] The surface tension of the ink composition is preferably suitable for inkjet printing, specifically, preferably in the range of 20 to 40 mN / m, more preferably 25 to 35 mN / m. By setting the surface tension within this range, flight bending can be suppressed. It should be noted that flight bending refers to a deviation of more than 30 μm from the target position when the ink composition is ejected from the ink ejection orifice. When the surface tension is 40 mN / m or less, the meniscus shape at the leading edge of the ink ejection orifice is stable, thus making it easier to control the ejection of the ink composition (e.g., control of ejection amount and ejection timing). On the other hand, when the surface tension is 20 mN / m or less, flight bending can be suppressed. That is, the following situations will not occur: the ink composition does not land correctly in the pixel formation area where it should land, resulting in insufficiently filled pixels, or the ink composition lands in a pixel formation area (or pixel) adjacent to the pixel formation area where it should land, resulting in reduced color reproducibility.

[0167] The ink composition may further contain components other than luminescent nanocrystal particles, light-scattering particles, photopolymerizable compounds, thermosetting resins, polymeric dispersants, polymerization initiators, and organic ligands, without impairing the effects of the present invention. Examples of such components include sensitizers and solvents.

[0168] [Sensitizer]

[0169] As sensitizers, amines that do not undergo addition reactions with photopolymerizable compounds can be used. Examples of sensitizers include trimethylamine, methyldiethanolamine, triethanolamine, p-diethylaminoacetophenone, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylbenzylamine, and 4,4'-bis(diethylamino)benzophenone.

[0170] [Organic solvents]

[0171] Examples of organic solvents include ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol dibutyl ether, diethyl adipate, dibutyl oxalate, dimethyl malonate, diethyl malonate, dimethyl succinate, diethyl succinate, 1,4-butanediol diacetate, and triacetylglycerol.

[0172] When formulating the ink composition of the present invention, in addition to the photopolymerizable compound, an organic solvent may be further contained. Regarding the boiling point of the organic solvent, from the viewpoint of the continuous ejection stability of the inkjet ink, it is preferably 180°C or higher. Furthermore, when forming the pixel portion, it is necessary to remove the organic solvent from the ink composition before curing; therefore, from the viewpoint of easy solvent removal, the boiling point of the solvent is preferably 300°C or lower.

[0173] When formulating the ink composition of the present invention, by selecting a liquid substance as the photopolymerizable compound and using it as the ink composition, a solvent-free ink composition that does not contain organic solvents as described above (not corresponding to photopolymerizable compounds) can be formulated. Regarding the solvent-free ink composition, the volume change during drying in the presence of organic solvents is small, which is beneficial for forming a thick ink film. Specifically, compared to ink compositions containing organic solvents, ink compositions without organic solvents have the following advantages: when obtaining a film of the same thickness, the amount of ink composition applied or the number of coatings can be reduced. If possible, using an ink composition without organic solvents as described above is preferred for the following reasons: not only is a process for removing the organic solvent not required before obtaining the cured product, but it is also less likely to cause defects in the ink film before curing, such as those that may occur during the removal of organic solvents; there is no need to worry about the emission of organic solvents into the atmosphere as a cause of environmental degradation; and equipment for the recycling and reuse of organic solvents is no longer required. As the photopolymerizable compound, a substance in a liquid state at room temperature is more preferred, but if it is a liquid state not exceeding 60°C, it is preferred because it can be liquefied by simple heating.

[0174] Moisture content

[0175] In the ink composition of the present invention, the moisture content of the ink composition can be determined by a Karl Fischer moisture analyzer (e.g., Mitsubishi Chemical Corporation, model CA-06, vaporization unit VA-06). From the viewpoint of suppressing the deterioration of luminescent nanocrystals, the moisture content in the ink composition can be 90 ppm or less, 50 ppm or less, 20 ppm or less, 9 ppm or less, 4 ppm or less, 2 ppm or less, or 1 ppm or less.

[0176] In the ink composition of the present invention, setting the moisture content range to the aforementioned range based on the use of a photopolymerizable compound with a specific LogP value range is more preferable from the viewpoint that: adverse conditions caused by cured material are less likely to occur, and the deterioration of luminescent nanocrystals can be more effectively suppressed. In the case of inkjet ink compositions, this complements the ejection method, and optimal technical effects can be expected.

[0177] In this invention, the moisture content of ink composition raw materials such as ink compositions and photopolymerizable compounds can be controlled within the specific content range mentioned above by the following methods. For example, this can be used to formulate ink compositions using photopolymerizable compounds that have been dehydrated by incorporating molecular sieves, or to add molecular sieves to ink compositions incorporating photopolymerizable compounds and then filter them after dehydration. If necessary, the filtration process described above may be omitted.

[0178] There is no particular limitation on the dehydration time, but since the molecular sieve requires time to adsorb water molecules contained in ink composition raw materials such as ink compositions and photopolymerizable compounds, dehydration can be carried out for more than 12 hours, 24 hours, or even 48 hours after adding the molecular sieve. In this case, dehydration can be carried out under an atmospheric atmosphere, preferably under a non-reactive gas atmosphere that is substantially free of moisture. It should be noted that the molecular sieve used is preferably used after removing the adsorbed water through heat treatment or the like before use. The heating temperature can be above 200°C, 250°C, 300°C, or 350°C. From the viewpoint of removing adsorbed water molecules, it is also preferable to reduce the pressure during heating, which can be below 0.1 mmHg, 0.01 mmHg, or 0.001 mmHg.

[0179] Solid raw materials such as light-scattering particles can adsorb water molecules in the atmosphere, so they can be dehydrated before use, or the moisture can be removed by heating in the atmosphere, under an inactive gas atmosphere, or under reduced pressure.

[0180] Moisture dissolves in liquids in the atmosphere, so the ink composition can be prepared by dehydrating the raw materials separately, or the ink composition can be prepared without dehydrating the raw materials and then dehydrated. Alternatively, the ink composition can be further dehydrated after separately dehydrating the raw materials. By performing a more rigorous dehydration process, adverse conditions caused by curing are less likely to occur, and the degradation of luminescent nanocrystals can be more effectively suppressed.

[0181] [Dissolved oxygen concentration]

[0182] In one embodiment, the dissolved oxygen concentration of ink composition raw materials such as ink compositions and photopolymerizable compounds can be reduced by exposing the ink or photopolymerizable compounds to a stream of inactive gas such as nitrogen or argon, or by blowing in an inactive gas. Regarding solid raw materials such as light-scattering particles, oxygen incorporation into the ink composition can also be suppressed by filling the container with a nitrogen stream and storing it under a nitrogen atmosphere.

[0183] The dissolved oxygen concentration is a value obtained by measuring the dissolved oxygen in the ink composition using an optical, solvent-resistant dissolved oxygen meter, specifically, the Hamilton Visiferm, for example, can be used to measure the dissolved oxygen concentration of the ink composition. It should be noted that it is also an embodiment of the present invention that the dissolved oxygen concentration can be reduced to a level lower than the measurable limit of the device used to measure the dissolved oxygen concentration.

[0184] As a method for removing dissolved gases, including dissolved oxygen and other gases, from the ink composition, conventionally known methods can be employed. Specifically, methods such as reducing pressure in the ink composition to remove dissolved gases including dissolved oxygen, and adding a deoxidizer to the ink composition can be cited.

[0185] [Oxygen absorber]

[0186] One embodiment of the ink composition contains a deoxidizing agent, which is any substance that reacts with dissolved oxygen to reduce the oxygen concentration. Examples of deoxidizing agents include L-ascorbic acid, isoascorbic acid, gallic acid and their salts, pyrogallol, galloacetophenone, etc.

[0187] Furthermore, regarding the content of the deoxidizer in the ink composition in this invention, in order to suppress the deterioration of luminescent nanocrystals, it can be 0.01% by mass or more, or 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more; in order to avoid coloring of the ink curing film, it can be 30% by mass or less, or 20% by mass or less, or 10% by mass or less, or 5% by mass or less.

[0188] As a method for removing dissolved gases from an ink composition, the following methods are preferred due to their simplicity: introducing an inactive gas such as nitrogen into the ink composition to remove dissolved gases containing dissolved oxygen, or reducing the pressure of the ink composition.

[0189] It should be noted that by combining the above-described method for removing dissolved gases containing dissolved oxygen from the ink composition with the above-described method for dehydrating the ink composition, an ink composition with low dissolved gas concentration and low moisture concentration can be prepared. From the viewpoint of being able to more effectively suppress the defects of the cured product and the deterioration of the luminescent nanocrystals, this is more preferable.

[0190] The above description describes one embodiment of the ink composition for color filters, but the ink composition of the above embodiment can also be used by methods other than inkjet printing, such as photolithography. In this case, the ink composition contains an alkali-soluble resin as a binder polymer.

[0191] When using an ink composition via photolithography, the ink composition is first coated onto a substrate. If the ink composition contains a solvent, it is then dried to form a coating film. This resulting coating film is soluble in an alkaline developer and is patterned by treatment with the alkaline developer. In this case, considering the ease of waste disposal of the developer, the alkaline developer is usually an aqueous solution; therefore, the coating film of the ink composition is treated with an aqueous solution. On the other hand, in ink compositions using luminescent nanocrystal particles (quantum dots, etc.), the luminescent nanocrystal particles are unstable in water, and their luminescence (e.g., fluorescence) is impaired by moisture. Therefore, in this embodiment, inkjet printing methods that do not require treatment with an alkaline developer (aqueous solution) are preferred.

[0192] Furthermore, even when the coating film of the ink composition is not treated with an alkaline developer, if the ink composition is alkali-soluble, the coating film easily absorbs moisture from the atmosphere, and over time, the luminescence (e.g., fluorescence) of the luminescent nanocrystal particles (quantum dots, etc.) gradually deteriorates. From this perspective, in this embodiment, the coating film of the ink composition is preferably alkali-insoluble. That is, the ink composition of this embodiment is preferably an ink composition capable of forming an alkali-insoluble coating film. Such an ink composition can be obtained by using an alkali-insoluble photopolymerizable compound as the photopolymerizable compound. "Alkali-insoluble" means that, based on the total mass of the ink composition coating film, the solubility of the ink composition coating film at 25°C relative to a 1% by mass potassium hydroxide aqueous solution is 30% by mass or less. The aforementioned solubility of the ink composition coating film is preferably 10% by mass or less, more preferably 3% by mass or less. It should be noted that the ink composition being an ink composition capable of forming an alkali-insoluble coating film can be confirmed by measuring the above-mentioned solubility in a coating film with a thickness of 1 μm obtained by applying the ink composition to a substrate and drying it at 80°C for 3 minutes with a solvent.

[0193] <Method for manufacturing ink composition>

[0194] Next, a method for manufacturing the ink composition according to the above-described embodiments will be described. The method for manufacturing the ink composition includes, for example, a first step of preparing a dispersion of light-scattering particles containing light-scattering particles and a polymeric dispersant, and a second step of mixing the dispersion of light-scattering particles with luminescent nanocrystal particles. In this method, the dispersion of light-scattering particles may further contain a photopolymerizable compound having a specific LogP value range as described above as an essential component, and in the second step, the photopolymerizable compound may be further mixed. According to this method, the light-scattering particles can be sufficiently dispersed. Therefore, an ink composition that reduces light leakage in the pixel area can be easily obtained.

[0195] In the process of preparing a dispersion of light-scattering particles, the dispersion can be prepared by mixing and dispersing the light-scattering particles with a polymeric dispersant and, depending on the case, a photopolymerizable compound. The mixing and dispersion can be performed using dispersion equipment such as a bead mill, a paint mixer, or a planetary mixer. From the viewpoint of achieving good dispersibility of the light-scattering particles and easily adjusting the average particle size of the light-scattering particles to the desired range, a bead mill or a paint mixer is preferred.

[0196] The method for manufacturing the ink composition may further include a step of preparing a dispersion of luminescent nanocrystal particles containing luminescent nanocrystal particles and a photopolymerizable compound before the second step. In this case, the dispersion of light-scattering particles and the dispersion of luminescent nanocrystal particles are mixed in the second step. Using this method, the luminescent nanocrystal particles can be sufficiently dispersed. Therefore, an ink composition that reduces light leakage in the pixel area can be easily obtained. In the step of preparing the dispersion of luminescent nanocrystal particles, the same dispersion apparatus used in the step of preparing the dispersion of light-scattering particles can be used to perform the mixing and dispersion treatment of the luminescent nanocrystal particles and the photopolymerizable compound.

[0197] The resulting ink composition can be formulated as described above, according to a specific moisture content.

[0198] When using the ink composition of this embodiment as an ink composition for inkjet printing, it is preferable to apply a piezoelectric inkjet recording device, which utilizes a mechanical ejection mechanism employing piezoelectric elements. In piezoelectric inkjet printing, the ink composition is not instantly exposed to high temperatures during ejection, making it less likely to cause deterioration of the luminescent nanocrystal particles, and making it easier to obtain the same luminescent properties desired in the color filter pixel section (light conversion layer).

[0199] <Light conversion layer and color filter>

[0200] Next, details of the light conversion layer and color filter using the ink composition of the above-described embodiment will be described with reference to the accompanying drawings. It should be noted that in the following description, the same or corresponding elements will be referred to by the same reference numerals, and repeated descriptions will be omitted.

[0201] Figure 1 This is a schematic cross-sectional view of a color filter according to one embodiment. Figure 1 As shown, the color filter 100 includes a substrate 40 and a light conversion layer 30 disposed on the substrate 40. The light conversion layer 30 has a plurality of pixel portions 10 and light-blocking portions 20.

[0202] The light conversion layer 30 has a first pixel portion 10a, a second pixel portion 10b, and a third pixel portion 10c as pixel portions 10. The first pixel portion 10a, the second pixel portion 10b, and the third pixel portion 10c are arranged in a grid pattern in a sequential repeating manner. Light-shielding portions 20 are disposed between the pixel portions, that is, between the first pixel portion 10a and the second pixel portion 10b, between the second pixel portion 10b and the third pixel portion 10c, and between the third pixel portion 10c and the first pixel portion 10a. In other words, these adjacent pixel portions are separated from each other by the light-shielding portions 20.

[0203] The first pixel portion 10a and the second pixel portion 10b each contain a cured product of the ink composition of the above embodiment. The cured product contains luminescent nanocrystal particles, light-scattering particles, and a curing component. The curing component is a cured product of a photopolymerizable compound; specifically, it is a cured product obtained by polymerization of a photopolymerizable compound. That is, the first pixel portion 10a contains a first curing component 13a, and first luminescent nanocrystal particles 11a and first light-scattering particles 12a dispersed in the first curing component 13a. Similarly, the second pixel portion 10b contains a second curing component 13b, and second luminescent nanocrystal particles 11b and second light-scattering particles 12b dispersed in the second curing component 13b. In the first pixel portion 10a and the second pixel portion 10b, the first curing component 13a and the second curing component 13b may be the same or different, and the first light-scattering particles 12a and the second light-scattering particles 12b may be the same or different.

[0204] The first luminescent nanocrystal particle 11a is a red luminescent nanocrystal particle that absorbs light with wavelengths in the range of 420-480 nm and emits light with a peak emission wavelength in the range of 605-665 nm. In other words, the first pixel unit 10a is a red pixel unit for converting blue light into red light. Furthermore, the second luminescent nanocrystal particle 11b is a green luminescent nanocrystal particle that absorbs light with wavelengths in the range of 420-480 nm and emits light with a peak emission wavelength in the range of 500-560 nm. In other words, the second pixel unit 10b is a green pixel unit for converting blue light into green light.

[0205] Regarding the content of luminescent nanocrystal particles in the pixel portion of the cured ink composition, from the viewpoint of achieving a superior light leakage reduction effect, based on the total mass of the cured ink composition, it can be 5% by mass or more, or 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 30% by mass or more, or 40% by mass or more. Regarding the content of luminescent nanocrystal particles, from the viewpoint of achieving excellent pixel portion reliability, based on the total mass of the cured ink composition, it can be 70% by mass or less, or 60% by mass or less, or 55% by mass or less, or 50% by mass or less.

[0206] Regarding the content of light-scattering particles in the pixel portion of the cured ink composition, from the viewpoint of achieving a better light leakage reduction effect, based on the total mass of the cured ink composition, it can be 0.1% by mass or more, or 1% by mass or more, or 5% by mass or more, or 7% by mass or more, or 10% by mass or more, or 12% by mass or more. Regarding the content of light-scattering particles, from the viewpoint of achieving a better light leakage reduction effect and achieving better pixel portion reliability, based on the total mass of the cured ink composition, it can be 60% by mass or less, or 50% by mass or less, or 40% by mass or less, or 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less. Regarding the content of light-scattering particles, based on the total mass of the cured ink composition, it can be 0.1~60% by mass, 0.1~50% by mass, 0.1~40% by mass, 0.1~30% by mass, 0.1~25% by mass, 0.1~20% by mass, 0.1~15% by mass, 1~60% by mass, 1~50% by mass, 1~40% by mass, 1~30% by mass, 1~25% by mass, 1~20% by mass, 1~15% by mass, 5~60% by mass, 5~50% by mass, 5~40% by mass, 5~30% by mass, and 5~25% by mass. 5~20% by mass, 5~15% by mass, 7~60% by mass, 7~50% by mass, 7~40% by mass, 7~30% by mass, 7~25% by mass, 7~20% by mass, 7~15% by mass, 10~60% by mass, 10~50% by mass, 10~40% by mass, 10~30% by mass, 10~25% by mass, 10~20% by mass, 10~15% by mass, 12~60% by mass, 12~50% by mass, 12~40% by mass, 12~30% by mass, 12~25% by mass, 12~20% by mass, or 12~15% by mass.

[0207] The third pixel portion 10c has a transmittance of 30% or more for light with wavelengths in the range of 420-480 nm. Therefore, the third pixel portion 10c functions as a blue pixel portion when using a light source that emits light with wavelengths in the range of 420-480 nm. The third pixel portion 10c, for example, comprises a cured product of a composition containing the aforementioned photopolymerizable compound. The cured product contains a third curing component 13c. The third curing component 13c is a cured product of a photopolymerizable compound; specifically, it is a cured product obtained by polymerization of the photopolymerizable compound. That is, the third pixel portion 10c comprises the third curing component 13c. When the third pixel portion 10c contains the aforementioned cured product, provided that the transmittance for light with wavelengths in the range of 420-480 nm is 30% or more, the composition containing the photopolymerizable compound may further contain components other than the photopolymerizable compound in the components contained in the aforementioned ink composition. It should be noted that the transmittance of the third pixel portion 10c can be measured using a microspectroscopic apparatus.

[0208] The thickness of the pixel portion (first pixel portion 10a, second pixel portion 10b, and third pixel portion 10c) can be, for example, 1 μm or more, 2 μm or more, or 3 μm or more. The thickness of the pixel portion (first pixel portion 10a, second pixel portion 10b, and third pixel portion 10c) can be, for example, 30 μm or less, 20 μm or less, or 15 μm or less.

[0209] The light-shielding portion 20 is a so-called black matrix provided to separate adjacent pixel portions to prevent color mixing and to prevent light leakage from the light source. The material constituting the light-shielding portion 20 is not particularly limited; besides metals such as chromium, cured products of resin compositions containing light-shielding particles such as carbon microparticles, metal oxides, inorganic pigments, and organic pigments in the adhesive polymer can be used. As the adhesive polymer used here, substances made by mixing one or more types of resins such as polyimide resin, acrylic resin, epoxy resin, polyacrylamide, polyvinyl alcohol, gelatin, casein, and cellulose, photosensitive resins, and O / W emulsified resin compositions (e.g., substances emulsified with reactive silicone) can be used. The thickness of the light-shielding portion 20 can be, for example, 0.5 μm or more, or 10 μm or less.

[0210] The substrate 40 is a transparent substrate with light transmittance, and can be made of transparent glass substrates such as quartz glass, Pyrex (registered trademark) glass, and synthetic quartz sheets, transparent resin films, and optical resin films, etc., as well as transparent flexible substrates. Among these, a glass substrate made of alkali-free glass that does not contain alkali components is preferred. Specifically, Corning's "7059 glass," "1737 glass," "Eagle 200," and "Eagle XG," Asahi Glass's "AN100," and Nippon Electric Glass's "OA-10G" and "OA-11" are suitable. These are materials with low coefficients of thermal expansion, excellent dimensional stability, and good handling properties during high-temperature heat treatment.

[0211] The color filter 100 equipped with the light conversion layer 30 is suitable for use with light sources that emit light in the wavelength range of 420~480nm.

[0212] The color filter 100 can be manufactured, for example, by forming a pattern of the light-shielding portion 20 on the substrate 40, selectively adhering the ink composition (inkjet ink) of the above embodiment to the pixel area divided by the light-shielding portion 20 on the substrate 40 by inkjet spraying, and curing the ink composition by irradiation or heating with active energy rays.

[0213] Methods for forming the light-shielding portion 20 include forming a metal thin film such as chromium or a thin film of a resin composition containing light-shielding particles in the boundary region between multiple pixel portions on one side of the substrate 40, and then patterning the thin film. The metal thin film can be formed by, for example, sputtering or vacuum evaporation, while the thin film of the resin composition containing light-shielding particles can be formed by, for example, coating or printing. As a method for patterning, photolithography is an example.

[0214] Examples of inkjet printing methods include Bubble Jet (registered trademark), which uses an electrothermal converter as an energy-generating element, and piezoelectric jetting, which uses a piezoelectric element.

[0215] When curing the ink composition by irradiation with active energy rays (such as ultraviolet light), mercury lamps, metal halide lamps, xenon lamps, LEDs, etc., can be used. The wavelength of the irradiated light can be, for example, above 200 nm or below 440 nm. The exposure dose can be, for example, 10 mJ / cm². 2 The above can also be 4000mJ / cm 2 the following.

[0216] When curing the ink composition by heating, the heating temperature can be, for example, above 110°C or below 250°C. The heating time can be, for example, above 10 minutes or below 120 minutes.

[0217] The above describes one embodiment of the color filter, the light conversion layer, and their manufacturing method, but the present invention is not limited to the above embodiment.

[0218] For example, in the light conversion layer, a pixel portion (blue pixel portion) containing a cured ink composition may be provided instead of the third pixel portion 10c or based on the third pixel portion 10c. This cured ink composition contains blue luminescent nanocrystal particles. Alternatively, the light conversion layer may also have a pixel portion (e.g., a yellow pixel portion) containing a cured ink composition, which contains nanocrystal particles that emit light of colors other than red, green, and blue. In these cases, the luminescent nanocrystal particles contained in each pixel portion of the light conversion layer preferably have wavelengths of maximum absorption in the same wavelength region.

[0219] In addition, at least a portion of the pixel portion of the light conversion layer may also contain a cured composition of a pigment other than luminescent nanocrystal particles.

[0220] Furthermore, the color filter can have an ink-repellent layer, narrower than the width of the light-shielding area, made of an ink-repellent material on the pattern of the light-shielding portion. In addition to providing an ink-repellent layer, a photocatalyst layer, serving as a variable wettability layer, can be formed and coated in the region including the pixel formation area. Then, the photocatalyst layer is exposed to light through a photomask to selectively increase the ink affinity of the pixel formation area. Examples of photocatalysts include titanium dioxide.

[0221] In addition, the color filter can have an ink-receptor layer containing hydroxypropyl cellulose or the like between the substrate and the pixel.

[0222] Furthermore, the color filter may have a protective layer on the pixel portion. This protective layer is provided to prevent the leaching of components contained in the pixel portion, or components contained in the pixel portion and components contained in the photocatalyst layer, into the liquid crystal layer while planarizing the color filter. The material constituting the protective layer can be any known material used for protective layers of color filters.

[0223] Furthermore, regarding the manufacture of color filters and light conversion layers, pixel portions can be formed not only by inkjet printing but also by photolithography. In this case, an ink composition is first coated onto a substrate in a layered manner to form an ink composition layer. Next, the ink composition layer is exposed in a patterned manner and then developed using a developer. In this way, pixel portions composed of a cured ink composition are formed. The developer is usually alkaline, so an alkali-soluble polymer can be used as the binder polymer. However, from the viewpoint of material utilization efficiency, inkjet printing is superior to photolithography. This is because, in principle, photolithography removes almost two-thirds or more of the material, resulting in material waste. Therefore, in this embodiment, it is preferable to use inkjet ink to form pixel portions by inkjet printing.

[0224] Furthermore, in addition to containing the aforementioned luminescent nanocrystal particles, the pixel portion of the light conversion layer in this embodiment may further contain a pigment of approximately the same color as the emission color of the luminescent nanocrystal particles. For example, when using a pixel portion containing luminescent nanocrystal particles that absorb blue light and emit light as the pixel portion of a liquid crystal display element, if blue light to quasi-white light with a peak at 450 nm is used as the light from the light source, and the concentration of luminescent nanocrystal particles in the pixel portion is insufficient, light from the light source will pass through the light conversion layer when the liquid crystal display element is driven. The transmitted light (blue light, light leakage) from the light source and the light emitted by the luminescent nanocrystal particles will mix. From the viewpoint of preventing the reduction in color reproducibility caused by such color mixing, the pixel portion of the light conversion layer may contain pigment. In order to contain pigment in the pixel portion, pigment may be contained in the ink composition.

[0225] Furthermore, one or both of the red pixel portion (R), green pixel portion (G), and blue pixel portion (B) in the light conversion layer of this embodiment can be configured as pixel portions containing color materials but without luminescent nanocrystal particles. Known color materials can be used here. For example, for the color material used in the red pixel portion (R), diketopyrrole pigments and / or anionic red organic dyes can be listed. For the color material used in the green pixel portion (G), at least one selected from the group consisting of copper halide phthalocyanine pigments, phthalocyanine green dyes, phthalocyanine blue dyes, and azo yellow organic dyes can be listed. For the color material used in the blue pixel portion (B), ε-type copper phthalocyanine pigments and / or cationic blue organic dyes can be listed. Regarding the amount of these color materials used, from the viewpoint of preventing a decrease in transmittance when contained in the light conversion layer, based on the total mass of the pixel portion (cured ink composition), 1 to 5% by mass is preferred.

[0226] Example

[0227] The present invention will be specifically described below through embodiments. However, the present invention is not limited to the embodiments described below.

[0228] The following operations for manufacturing luminescent nanocrystals and inks are carried out in a glove box filled with nitrogen or in a flask under nitrogen flow that blocks the atmosphere.

[0229] Furthermore, all raw materials listed below are used after nitrogen has been pre-introduced into the container to replace the atmospheric atmosphere within it. It should be noted that, for liquid materials, nitrogen is introduced into the liquid to replace dissolved oxygen.

[0230] In addition, the chloroform, ethanol, hexane, toluene, epoxy monomers, and oxetane monomers used below were pre-dehydrated and dried using molecular sieves (basically 3A, and 4A for hexane and toluene) for more than 48 hours.

[0231] Regarding titanium oxide, before use, it should be heated at 120°C for 2 hours under a reduced pressure of 1 mmHg, and then naturally cooled under a nitrogen atmosphere.

[0232] [Manufacturing of Red Luminescent Nanocrystals]

[0233] In a 1000 ml flask, add 17.48 g of indium acetate, 25.0 g of trioctylphosphine oxide, and 35.98 g of lauric acid. Stir at 160°C for 40 minutes while bubbling with nitrogen. Further stir at 250°C for 20 minutes, then heat to 300°C and continue stirring. Dissolve 4.0 g of tris(trimethylsilyl)phosphine in 15.0 g of trioctylphosphine in a glove box and fill a glass syringe. Inject this solution into the flask maintained at 300°C and allow it to react at 250°C for 10 minutes. Further, in a glove box, add 5 ml of a mixture containing 7.5 g of tris(trimethylsilyl)phosphine dissolved in 30.0 g of trioctylphosphine dropwise over 12 minutes, then add 5 ml at 15-minute intervals until the mixture is used up.

[0234] In another three-necked flask, 5.595 g of indium acetate, 10.0 g of trioctylphosphine oxide, and 11.515 g of lauric acid were added. The mixture was stirred at 160°C for 40 minutes while bubbling with nitrogen. The mixture was then stirred further at 250°C for 20 minutes, heated to 300°C, and cooled to 70°C. The resulting mixed solution was added to the above reaction solution. In a glove box, 5 ml of a mixture of 4.0 g of tris(trimethylsilyl)phosphine dissolved in 15.0 g of trioctylphosphine was added dropwise to the above reaction solution every 12 minutes. This was repeated every 15 minutes until the mixture was completely used. Stirring was maintained for 1 hour. After cooling to room temperature, 100 ml of toluene and 400 ml of ethanol were added to cause particle aggregation. The particles were precipitated using a centrifuge, and the supernatant was discarded. The precipitated particles were dissolved in trioctylphosphine to obtain a trioctylphosphine solution of indium phosphide (InP) red luminescent nanocrystals.

[0235] [Fabrication of Green Luminescent Nanocrystals]

[0236] In a 1000 ml flask, 23.3 g of indium acetate, 40.0 g of trioctylphosphine oxide, and 48.0 g of lauric acid were added. The mixture was stirred at 160 °C for 40 minutes while bubbling with nitrogen. After further stirring at 250 °C for 20 minutes, the mixture was heated to 300 °C and stirred continuously. In a glove box, 10.0 g of tris(trimethylsilyl)phosphine was dissolved in 30.0 g of trioctylphosphine and the solution was filled into a glass syringe. This solution was injected into the flask stored at 300 °C and reacted at 250 °C for 5 minutes. The flask was cooled to room temperature, and 100 ml of toluene and 400 ml of ethanol were added to cause particle aggregation. The particles were precipitated using a centrifuge, and the supernatant was discarded. The precipitated particles were then dissolved in trioctylphosphine to obtain a trioctylphosphine solution of indium phosphide (InP) green luminescent nanocrystals.

[0237] [Fabrication of InP / ZnS core-shell nanocrystals]

[0238] In a 1000 ml flask, 3.6 g of InP and 90 g of trioctylphosphine were prepared from the above-synthesized InP nanocrystals and added to a trioctylphosphine oxide solution. 90 g of trioctylphosphine oxide and 30 g of lauric acid were then added. Meanwhile, a stock solution was prepared by mixing 42.9 ml of a 1M hexane solution of diethylzinc, 92.49 g of a 9.09 wt% solution of trioctylphosphine in bis(trimethyl)sulfide, and 162 g of trioctylphosphine in a glove box. The flask was then purged with nitrogen, and the temperature was set to 180°C. At 80°C, 15 ml of the stock solution was added, followed by 15 ml every 10 minutes (while maintaining the flask temperature at 180°C). After the final addition, the temperature was maintained for another 10 minutes to complete the reaction. After the reaction, the solution was cooled to room temperature, and 500 ml of toluene and 2000 ml of ethanol were added to cause the nanocrystals to condense. After precipitating the nanocrystals using a centrifuge, the supernatant was discarded. The precipitate was then redissolved in chloroform to obtain a chloroform solution of InP / ZnS core-shell nanocrystals, with the nanocrystal concentration in the solution reaching 20% ​​by mass.

[0239] [QD ligand exchange]

[0240] Referring to Japanese Patent Application Publication No. 2002-121549, a triethylene glycol monomethyl ether ester of 3-mercaptopropionic acid (TEGMEMP) was synthesized.

[0241] In a nitrogen-filled container, QD dispersion 1 (the above InP / ZnS core-shell nanocrystals (red luminescent)) was mixed with 80g of chloroform solution obtained by dissolving 8g of the above-synthesized TEGMEMP. The mixture was stirred at 80°C for 2 hours to carry out ligand exchange, and then cooled to room temperature.

[0242] Then, toluene / chloroform was evaporated under reduced pressure and stirred at 40°C, concentrating the liquid to 100 ml. Four times its weight of n-hexane was added to the dispersion to coagulate the QD, and the supernatant was removed by centrifugation and decantation. 50 g of toluene was added to the precipitate, and it was redispersed by ultrasonication. This washing operation was performed three times to remove any remaining free ligand components in the liquid. The decanted precipitate was vacuum dried at room temperature for 2 hours to obtain 2 g of TEGMEMP-modified QD (QD-TEGMEMP) powder.

[0243] [Preparation of QD / Alicyclic Epoxy Monomer Dispersion 1]

[0244] In a nitrogen-filled container, 2g of the above-mentioned QD-TEGMEMP was mixed with 8g of alicyclic epoxy monomer, and then dispersed by ultrasound to obtain QD / alicyclic epoxy monomer dispersion 1 (QD content: 20% by mass).

[0245] [Preparation of Titanium Oxide Dispersion]

[0246] In a nitrogen-filled container, 12.9 g of titanium dioxide, 1.3 g of polymeric dispersant, and 18.1 g of oxetine monomer were mixed. Zirconium beads (1.25 mm in diameter) were added to the nitrogen-filled container, and the sealed container was vibrated for 2 hours using a paint mixing machine to disperse the complex. Next, nitrogen was introduced to replace dissolved oxygen, resulting in light-scattering particle dispersion 1.

[0247] [Example 1]

[0248] [Preparation of ink composition]

[0249] In a nitrogen-filled container, 6.47g of QD / alicyclic epoxy monomer dispersion 1, 3.23g of the aforementioned light-scattering particle dispersion 1 and 0.3g of photocationic polymerization initiator were mixed. The mixture was then filtered in a glove box using a filter with a pore size of 5μm. Nitrogen gas was then introduced into the ink to saturate it with nitrogen.

[0250] Next, nitrogen gas is removed under reduced pressure to obtain the ink composition. It should be noted that the materials used are as follows.

[0251] [Light-scattering particles]

[0252] • Titanium oxide: JR-806 (trade name manufactured by TAYCA Corporation, average particle size (volume average diameter): 300 nm)

[0253] [Photopolymerizable compounds]

[0254] • Alicyclic epoxy monomer: LDO (trade name of Ba Kogyo Co., Ltd.)

[0255] • Oxybutane monomer: ARON OXETANE OXT-221 (trade name manufactured by Toa Synthetic Co., Ltd., "ARONOXETANE" is a registered trademark)

[0256] [Polymer Dispersant]

[0257] • Polymer dispersant: DISPERBYK-2155 (trade name manufactured by BYK Corporation; "DISPERBYK" is a registered trademark)

[0258] [Polymerization initiator]

[0259] • Photocationic polymerization initiator: CPI-100P (trade name manufactured by San-Apro Co., Ltd., "CPI" is a registered trademark)

[0260] Of the above materials, the liquid material was pre-dehydrated using molecular sieve 3A for more than 48 hours before mixing. Regarding titanium oxide, it was heated at 120°C for 2 hours under reduced pressure of 1 mmHg before mixing, and then naturally cooled under a nitrogen atmosphere.

[0261] [Example 2]

[0262] [Preparation of ink composition]

[0263] In a nitrogen-filled container, QD / alicyclic epoxy monomer dispersion 2 (green luminescent) was used, and the process was otherwise the same as in Example 1 to obtain the ink composition.

[0264] [Comparative Example 1]

[0265] As a method for adjusting the ink composition, epoxy monomers shown in the table below that have not been dehydrated by molecular sieves were used, and the same procedure as in Example 1 was followed to obtain the ink composition.

[0266] (2) Fabrication of light conversion color filter

[0267] The ink composition obtained above was applied to a glass substrate using a spin coater to achieve a dried film thickness of 4 μm. After drying, the resulting film was coated with an ink using a spin coater at 2000 mJ / cm². 2 The light is irradiated with ultraviolet light. This causes the ink composition to cure, forming a layer (light conversion layer) composed of the cured ink composition on the glass substrate. Through the above operations, a light conversion color filter is obtained.

[0268] (3) Evaluation

[0269] The ink composition and the light conversion filter obtained above were evaluated according to the following steps. The results are shown in Table 1.

[0270] External quantum efficiency (EQE)

[0271] Using the aforementioned blue LED (peak emission wavelength: 450nm), an integrating sphere was connected to the aforementioned Otsuka Electronics Co., Ltd. radiometric spectrophotometer (trade name "MCPD-9800"), with the integrating sphere positioned above the blue LED. A substrate with a light conversion layer was inserted between the blue LED and the integrating sphere, the blue LED was lit, and the observed spectrum and illuminance at each wavelength were measured.

[0272] Using the spectrum and illuminance measured by the aforementioned measuring device, the external quantum efficiency is determined as described below. This value indicates the proportion of light (photons) incident on the light conversion layer that is emitted as fluorescence to the observer side. Therefore, the larger the value, the better the light conversion layer, and this value, along with S(PL), is an important evaluation indicator.

[0273] External quantum efficiency of the red light-emitting conversion layer = P(red) / E(blue) × 100 (%)

[0274] External quantum efficiency of the green light-emitting conversion layer = P(green) / E(blue) × 100 (%)

[0275] Here, E (blue), P (red), and P (green) represent the following contents respectively.

[0276] E (Blue):

[0277] This represents the total value of "illuminance × wavelength ÷ hc" in the wavelength range of 380–490 nm. It should be noted that h represents Planck's constant, and c represents the speed of light. (This value corresponds to the number of observed photons.)

[0278] P (Red):

[0279] This represents the total value of "illuminance × wavelength ÷ hc" in the measurement wavelength range of 490–590 nm within that wavelength region. (Corresponding to the number of photons observed)

[0280] P (Green):

[0281] This represents the total value of "illuminance × wavelength ÷ hc" in the measurement wavelength range of 590–780 nm. (Corresponding to the number of photons observed)

[0282] Based on the above, the EQE is calculated. The EQE of Example 2 is set to 10. The EQE of the measured sample is used as a relative value and evaluated as follows.

[0283] <Evaluation Criteria>

[0284] Less than 10: D

[0285] 10:C

[0286] Greater than 10 and less than 100: B

[0287] Cases greater than 100: A

[0288] [Bubble Evaluation]

[0289] Use a liquid delivery pump to deliver the aforementioned ink, and visually observe the generation of air bubbles in the piping.

[0290] [Moisture Content Evaluation]

[0291] Moisture content was determined using a Karl Fischer moisture analyzer (Mitsubishi Chemical Co., Ltd., model CA-06, vaporization unit VA-06, also manufactured by the same company).

[0292] [Table 1]

[0293]

[0294] [Example 3]

[0295] First, a substrate (BM substrate) with a light-shielding portion called a black matrix (BM) is fabricated according to the following steps. Specifically, a black resist (CFPR BK) is coated onto a glass substrate made of alkali-free glass (NEC-10G, manufactured by NEC Glass Co., Ltd.), followed by pre-baking, pattern exposure, development, and post-baking to form a patterned light-shielding portion. Exposure is performed on the black resist at 250 mJ / cm². 2 The light-shielding part is formed by irradiating ultraviolet light with an exposure amount. The pattern of the light-shielding part is a pattern with an opening corresponding to a 200μm × 600μm sub-pixel, with a line width of 20μm and a thickness of 2.6μm.

[0296] Next, the red luminescent ink composition obtained in Example 1 was printed onto the opening portion of the BM substrate using an inkjet printer. The substrate was then irradiated with ultraviolet light and subsequently heated at 150°C for 30 minutes under a nitrogen atmosphere. This cured the ink composition, forming a pixel portion composed of the cured ink composition. The resulting pixel portion converts blue light into red light. The thickness of the pixel portion is 2.1 μm. Through the above operations, a patterned light conversion filter was obtained.

[0297] [Example 4]

[0298] The BM substrate was prepared in the same manner as in Example 3. Next, the red luminescent ink composition obtained in Example 1 and the green luminescent ink composition obtained in Example 2 were printed onto the opening portion of the BM substrate using an inkjet printer. The substrate was then irradiated with ultraviolet light to cure the ink compositions in the same manner as in Example 3. This resulted in the formation of pixel portions that convert blue light to red light and pixel portions that convert blue light to green light on the BM substrate. Through these operations, a patterned light conversion color filter with multiple pixel portions was obtained.

[0299] Symbol Explanation

[0300] 10: Pixel part; 10a: First pixel part; 10b: Second pixel part; 10c: Third pixel part; 11a: First luminescent nanocrystal particle; 11b: Second luminescent nanocrystal particle; 12a: First light scattering particle; 12b: Second light scattering particle; 20: Light-shielding part; 30: Light conversion layer; 40: Substrate; 100: Color filter.

Claims

1. An ink composition for inkjet printing, characterized in that, It contains luminescent nanocrystal particles, photopolymerizable compounds, light-scattering particles, and polymeric dispersants. The photopolymerizable compound has a LogP value greater than -1.0 and less than 5.

0. Based on the mass of the non-volatile components in the ink composition, the content of luminescent nanocrystal particles in the ink composition is 5% by mass or more. Based on the mass of the non-volatile components in the ink composition, the content of light-scattering particles in the ink composition is 1% by mass or more. The photopolymerizable compound comprises alicyclic epoxy monomers and oxocyclic butane monomers. The polymeric dispersant has a weight-average molecular weight of 750 or higher and 30,000 or lower, and an acid value of 1-150 mg KOH / g or an amine value of 1-200 mg KOH / g. The viscosity of the ink composition for inkjet printing is 2~20 mPa·s. The ink composition for inkjet printing is for use with color filters.

2. The ink composition for inkjet printing according to claim 1, characterized in that, The alicyclic epoxy monomer is 1,2-epoxy-4-vinylcyclohexane. The oxetane monomer is 3-hydroxymethyl-3-ethyloxetane and / or OXT-221.

3. The ink composition for inkjet printing according to claim 1, characterized in that, Based on the mass of the non-volatile components in the ink composition, the content of luminescent nanocrystal particles in the ink composition is 10% by mass or more.

4. The ink composition for inkjet printing according to claim 1, characterized in that, The moisture content (H2O) measured using a Karl Fischer moisture analyzer is below 90 ppm.

5. The ink composition for inkjet printing according to claim 1, characterized in that, The moisture content (H2O) measured by the Karl Fischer moisture analyzer is below 20 ppm.

6. The ink composition for inkjet printing according to claim 1, characterized in that, The ink composition contains molecular sieves.

7. A method for manufacturing an ink composition for inkjet printing, comprising an ink composition containing luminescent nanocrystal particles, a photopolymerizable compound, light-scattering particles, and a polymeric dispersant, wherein the moisture content (H2O) as measured by a Karl Fischer moisture analyzer is 90 ppm or less. Its features are, The ink composition is depressurized to remove dissolved gases.

8. A light conversion layer comprising a cured product of the ink composition for inkjet printing according to any one of claims 1 to 6.

9. The light conversion layer according to claim 8, comprising a plurality of pixel units, The plurality of pixels have: The first pixel portion includes the solidified material and contains luminescent nanocrystal particles that absorb light with wavelengths in the range of 420-480 nm and emit light with a emission peak wavelength in the range of 605-665 nm as the luminescent nanocrystal particles; and The second pixel portion includes the solidified material and contains luminescent nanocrystal particles that absorb light with wavelengths in the range of 420-480 nm and emit light with a emission peak wavelength in the range of 500-560 nm.

10. A color filter comprising the light conversion layer of claim 8.

Citation Information

Patent Citations

  • Dispersing agent*dispersion liquid containing said agent and paint and ink made from said liquid

    JP1979037082A

  • Adduct, manufacture, dispersion and solid coated therewith

    JP1985166318A

  • Fine non-magnetic solid composition and dispersant

    JP1986174939A

  • Pigment dispersant

    JP1997169821A

  • Radiation sensitive composition

    JP1997171253A